KEMAMPUAN RASIO KEUANGAN DALAM MEMPREDIKSI PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2017 - Nuladani Setya Budi; Halimatusyadiah (UNIB Press, 2022)
The research aims to: (1) test and prove the ability of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), capability Operations on operating income (BOPO), Net Interest Margin (NIM), Return On Asset (ROA) and Return On Equity (ROE) in predicting profit growth Registered Banking Company in IDX. A research sample is a banking company listed on the Indonesia Stock Exchange. Data analysis methods use multiple linear regression analyses. From the research results are known that: (1) Capital Adequacy Ratio (CAR) is not able to predict the profit growth of registered banking companies in IDX: (2) Loan to Deposit Ratio (LDR) is not able to predict the profit growth of the banking company Registered in the IDX: (3) Non-Performing Loan (NPL) is not able to predict the profit growth of registered banking companies in IDX: (4) operating expenses on operating income (BOPO) is not able to predict the profit growth of the banking company Registered in IDX: (5) Net Interest Margin (NIM) is not able to predict the profit growth of registered banking companies in IDX: (7) Return On Equity (ROE) is able to predict the profit growth of the IDX-registered banking company. The research aims to: (1) test and prove the ability of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), capability Operations on operating income (BOPO), Net Interest Margin (NIM), Return On Asset (ROA) and Return On Equity (ROE) in predicting profit growth Registered Banking Company in IDX. A research sample is a banking company listed on the Indonesia Stock Exchange. Data analysis methods use multiple linear regression analyses. From the research results are known that: (1) Capital Adequacy Ratio (CAR) is not able to predict the profit growth of registered banking companies in IDX: (2) Loan to Deposit Ratio (LDR) is not able to predict the profit growth of the banking company Registered in the IDX: (3) Non-Performing Loan (NPL) is not able to predict the profit growth of registered banking companies in IDX: (4) operating expenses on operating income (BOPO) is not able to predict the profit growth of the banking company Registered in IDX: (5) Net Interest Margin (NIM) is not able to predict the profit growth of registered banking companies in IDX: (7) Return On Equity (ROE) is able to predict the profit growth of the IDX-registered banking company.